2018
DOI: 10.1037/cns0000159
|View full text |Cite
|
Sign up to set email alerts
|

Symptom self-reports are susceptible to misinformation.

Abstract: We examined whether self-reported symptoms are affected by explicit and implicit misinformation. In Experiment 1, undergraduates (N = 60) rated how often they experienced somatic and psychological symptoms. During a subsequent interview, they were exposed to misinformation about 2 of their ratings: One was inflated (upgraded misinformation), whereas another was deflated (downgraded misinformation). Close to 82% of the participants accepted the upward symptom misinformation, whereas 67% accepted the downward ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…However, participants who concurrently detected the misinformation did not exhibit a reduction in their pain ratings. These findings are consistent with past research demonstrating that people can be led to misremember their own reports on their internal states (Merckelbach et al, 2018), that choice blindness can have lasting effects for memory (i.e., memory blindness; Cochran et al, 2016;Stille et al, 2017), and that when people detect the discrepancy between misinformation and facts, they are less likely to be swayed by the misinformation (Tousignant, Hall, & Loftus, 1986). These findings add to the literature by demonstrating that memory blindness can be found in memory for a painful, lived experience, not just in symptoms on a checklist.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, participants who concurrently detected the misinformation did not exhibit a reduction in their pain ratings. These findings are consistent with past research demonstrating that people can be led to misremember their own reports on their internal states (Merckelbach et al, 2018), that choice blindness can have lasting effects for memory (i.e., memory blindness; Cochran et al, 2016;Stille et al, 2017), and that when people detect the discrepancy between misinformation and facts, they are less likely to be swayed by the misinformation (Tousignant, Hall, & Loftus, 1986). These findings add to the literature by demonstrating that memory blindness can be found in memory for a painful, lived experience, not just in symptoms on a checklist.…”
Section: Discussionsupporting
confidence: 92%
“…Nonblind participants showed no difference between manipulated and control symptoms at any time. A more recent article replicated these findings using a symptom checklist that included both psychological and somatic symptoms and demonstrated that participants could also be led to underestimate their symptom ratings as a result of misinformation (Merckelbach, Dalsklev, Van Helvoort, Boskovic, & Otgaar, 2018). These studies illustrate that people can be misinformed about their own internal states.…”
Section: Misinformation and Healthcarementioning
confidence: 79%
“…Our hypotheses and the analyses reported below were preregistered at Open Science Framework. Most analyses were confirmatory and in line with previous articles on the topic (Merckelbach et al, 2011, 2018). Tests that involved total CSDL scores, symptom-change scores from Test 1 to Test 2, DES-T scores, and/or TAS-20 scores were exploratory.…”
Section: Resultssupporting
confidence: 83%
“…In the current study, α was .63. Specifically, we measured self-reported trait alexithymia and dissociation because we suspected that these traits—associated with poor introspective monitoring—relate to susceptibility to symptom escalation (but see Merckelbach et al, 2018). Finally, participants completed an exit questionnaire that measured their ideas about the experiment, after which they were fully debriefed (see Table S1 in the Supplemental Material).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation